(54x+65y)+(-11x+45y)=

Simple and best practice solution for (54x+65y)+(-11x+45y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (54x+65y)+(-11x+45y)= equation:


Simplifying
(54x + 65y) + (-11x + 45y) = 0

Remove parenthesis around (54x + 65y)
54x + 65y + (-11x + 45y) = 0

Remove parenthesis around (-11x + 45y)
54x + 65y + -11x + 45y = 0

Reorder the terms:
54x + -11x + 65y + 45y = 0

Combine like terms: 54x + -11x = 43x
43x + 65y + 45y = 0

Combine like terms: 65y + 45y = 110y
43x + 110y = 0

Solving
43x + 110y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-110y' to each side of the equation.
43x + 110y + -110y = 0 + -110y

Combine like terms: 110y + -110y = 0
43x + 0 = 0 + -110y
43x = 0 + -110y
Remove the zero:
43x = -110y

Divide each side by '43'.
x = -2.558139535y

Simplifying
x = -2.558139535y

See similar equations:

| 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 | | [2x-6]-4=26 | | v^2=8v+2 | | 4*x=88 | | 3*x-18=2*x^2-18+x^2+3*x+9 | | 5x+12-4x-14=3 | | 5y-10+y+48=5y+40-1y | | 3m+5=2m+3 | | 5xy^2+2x^2+y^3=0 | | 2(t+5)=2 | | 12ab/a^2b^2/3b/2a | | 14-x+2x+5=180 |

Equations solver categories